INTEGRATING MARKET ALTERNATIVES INTO THE ECONOMIC THEORY OF OPTIMAL DETERRENCE. (5th April 2016) - Curry, Philip A.; Doyle, Matthew
Abstract : Leading economic models of crime assume that potential criminals achieve their ends by criminal means or not at all. We develop a framework in which potential criminals can also attain their objectives through voluntary trade. Our framework helps explain several features of the legal system that have proven to be problematic for the canonical approach: why optimal sanctions should be increasing in an individual's criminal history, and why necessity may be a partial defense in some situations. Finally, the inclusion of a voluntary trade option makes the maximization of a utilitarian welfare function identical to minimizing the costs of crime, implying that a long‐standing controversy in the literature is, in part, an artifact of the assumption that criminals face a binary choice set. ( JEL K42, D60, H00)